Ovulation potential of human chorionic gonadotropin versus GnRH - B.S. Buttrey; M.G. Burns; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 2006)
Experiments have shown human chorionic gonadotropin (hCG) to be more effective than GnRH as a means to induce ovulation of folli-cles. Dosages used, however, have differed greatly among experiments. A study was per-formed to determine the minimum effective dose of hCG needed to induce ovulation of ovarian follicles in dairy cows. Ovaries of Holstein cows were mapped by using transrec-tal ultrasonography 7 days before a bi-weekly pregnancy diagnosis. Cows were assigned randomly to treatments of saline, 100 Î¼g of GnRH (2 mL of Fertagyl, Intervet, Inc., Mills-boro, NJ), or 500, 1000, 2000, or 3000 IU of hCG (0.5, 1, 2, or 3 mL of Chorulon, Intervet, Inc., Millsboro, NJ). Ovarian structures were monitored again 7 days later, and the propor-tion of cows, and proportion of follicles ≥8 mm in diameter, that ovulated were recorded. A dose of at least 1000 IU of hCG resulted in a greater ovulatory response than saline, GnRH, or 500 IU of hCG.; Dairy Day, 2006, Kansas State University, Manhattan, KS, 2006;
Keywords: Dairy Day; 2006; Kansas Agricultural Experiment Station contribution; no. 07-118-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 965; Dairy; GnRH; hCG; Ovulation